2022
DOI: 10.24072/pcjournal.156
|View full text |Cite
|
Sign up to set email alerts
|

Functional correlates of immediate early gene expression in mouse visual cortex

Abstract: During visual development, response properties of layer 2/3 neurons in visual cortex are shaped by experience. Both visual and visuomotor experience are necessary to coordinate the integration of bottom-up visual input and top-down motor-related input. Whether visual and visuomotor experience engage different plasticity mechanisms, possibly associated with the two separate input pathways, is still unclear. To begin addressing this, we measured the expression level of three different immediate early genes (IEG)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…Consistently, we also observed an increase in the expression of the immediate early gene c-Fos in the primary visual cortex of an amyloid mouse model (Niraula et al, 2023). c-Fos is rapidly and transiently expressed following membrane depolarization and calcium influx in some neurons (Barth, Gerkin and Dean, 2004;Kawashima, Okuno and Bito, 2014;Mahringer et al, 2022;Morgan et al, 1987;Yap and Greenberg, 2018;Zangenehpour and Chaudhuri, 2002). Its low baseline expression, widespread expression profile, and close associations with learning and memory recall have made c-Fos + cell labeling an attractive tool for mapping and manipulating experience and memory associated neuronal ensembles (Barth, Gerkin and Dean, 2004;Guenthner et al, 2013;Liu et al, 2012;Reijmers et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Consistently, we also observed an increase in the expression of the immediate early gene c-Fos in the primary visual cortex of an amyloid mouse model (Niraula et al, 2023). c-Fos is rapidly and transiently expressed following membrane depolarization and calcium influx in some neurons (Barth, Gerkin and Dean, 2004;Kawashima, Okuno and Bito, 2014;Mahringer et al, 2022;Morgan et al, 1987;Yap and Greenberg, 2018;Zangenehpour and Chaudhuri, 2002). Its low baseline expression, widespread expression profile, and close associations with learning and memory recall have made c-Fos + cell labeling an attractive tool for mapping and manipulating experience and memory associated neuronal ensembles (Barth, Gerkin and Dean, 2004;Guenthner et al, 2013;Liu et al, 2012;Reijmers et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…While many studies have reported using these tools in the hippocampus, it has been noted that the labeling sensitivity of pyramidal neurons in the CA1 and CA3 regions is lower than that of the granule cells in the dentate gyrus when using TetTag or TRAP2 mice ( Deng et al, 2013 ; Leake et al, 2021 ). Additionally, neurons belonging to functionally distinct circuits tend to express different IEGs ( Mahringer et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo calcium imaging studies also found surprisingly weak correlations between the frequency or amplitude of calcium transients and FOS expression in individual neurons during learning (14)(15)(16). As its complex transcriptional regulation already suggests, FOS seems to be more than a simple reporter of intracellular calcium or spike frequency.…”
Section: Introductionmentioning
confidence: 98%
“…In cultured neurons, stimuli delivered in repetitive short bursts drive FOS more efficiently than long duration trains of single action potentials, but FOS induction was not correlated with intracellular calcium levels ( 1113 ). In vivo calcium imaging studies also found surprisingly weak correlations between the frequency or amplitude of calcium transients and FOS expression in individual neurons during learning ( 1416 ). As its complex transcriptional regulation already suggests, FOS seems to be more than a simple reporter of intracellular calcium or spike frequency.…”
Section: Introductionmentioning
confidence: 99%